Transcervical dissection of metastatic suprahyoid retropharyngeal lymph nodes from papillary thyroid carcinoma through three anatomical barriers. Issue 2 (February 2021) - Chen, S.; Yang, H.; Su, X.; Yang, A.; Liu, W.
Abstract: Papillary thyroid carcinoma (PTC) rarely metastasizes to the suprahyoid retropharyngeal lymph nodes (SRPLNs). Studies on SRPLN metastasis from PTC and a description of the dissection of the SRPLNs via the transcervical approach are rare in the literature. In this study, the cases of six patients diagnosed with PTC with SRPLN metastasis, who underwent dissection of the SRPLNs between 2001 and 2017, were reviewed retrospectively. A transcervical approach was applied for exposure and dissection of the SRPLNs in all patients. All patients were successfully treated by transcervical resection of the metastatic SRPLNs. No patient needed a mandibulotomy or presented severe complications. The median duration of follow-up after dissection of the SRPLNs was 83 months. No recurrence of SRPLN metastasis was identified during follow-up, and none of the patients died of the disease. Surgery might be the best treatment for SRPLN metastasis from PTC. The transcervical route to the retropharyngeal space is through three anatomical barriers, including the submandibular gland, the posterior belly of the digastric muscle, and the blood vessels branching from the external carotid artery and internal jugular vein. Surgical removal of metastatic SRPLNs through the transcervical approach was safe and effective.